TFR1 as a Biomarker of Pulmonary Fibrosis Development in COPD Patients - Wu Y; Jiang Y; Xiao B; Xie L; Zhou N; Zeng A; Liu C (International Journal of COPD)
Yuan Wu,1 Yu Jiang,2 Bin Xiao,3 Lijun Xie,1 Nanjiang Zhou,1 Aoguo Zeng,1 Cuizhong Liu1 1Department of General Medicine, Hunan Provincial People’s Hospital and The First-Affiliated of Hospital of Hunan Normal University, Changsha, 410005, People’s Republic of China; 2Institute of Emergency Medicine, Hunan Provincial Key Laboratory of Emergency and Critical Care Metabonomics, Hunan Provincial People’s Hospital and The First-Affiliated of Hospital of Hunan Normal University, Changsha, 410005, People’s Republic of China; 3Department of Radiology, Hunan Provincial People’s Hospital and The First-Affiliated of Hospital of Hunan Normal University, Changsha, 410005, People’s Republic of ChinaCorrespondence: Cuizhong Liu, Department of General Medicine, Hunan Provincial People’s Hospital and The First-Affiliated of Hospital of Hunan Normal University, No. 61, Jiefang Road, Furong Square, Changsha, 410005, People’s Republic of China, Email liucz190102@sina.comBackground: Ferroptosis is involved in chronic lung injury, including COPD and pulmonary fibrosis. In this study, we investigated the role of transferrin protein 1 (TFR1), as a ferroptosis marker, in the development of COPD-associated pulmonary fibrosis.Methods: The expression of TFR1 was elevated in 97 patients with COPD. The correlation analysis of the clinical characteristic was performed including the frequency of acute exacerbation, the fibrosis score, etc. and the expression of TFR1. Animal experiments were carried out to verify TFR1 expression in a rat COPD model.Results: The results showed that the expression of TFR1 was related to DLCO%, 6 MWT, GOLD grade, frequency of acute exacerbation and fibrosis score. Together, in the rat COPD model, higher TFR1 was related to a higher lung injury score and a higher lung fibrosis score.Conclusion: In summary, these results indicated that serum TFR1 levels related to the severity of pulmonary fibrosis in clinical practice and may provide a potential target for the treatment of pulmonary fibrosis development from patients with COPD in the future.Keywords: TFR1, COPD, pulmonary fibrosis, biomarker, ferroptosis